Crediting temporary forest carbon: Retrospective and empirical perspectives on accounting options - Galik, Christopher S.; Baker, Justin S.; Daigneault, Adam; Latta, Gregory (Frontiers in Forests and Global Change, 2022)
The costs and technical expertise associated with forest carbon offset projects can be significant, while decades-long time commitments can discourage participation from the outset. Considering these challenges, several new approaches have emerged in the United States under the auspices of both long-standing and recently-established programs, attempting to leverage increased carbon mitigation. What several of these approaches have in common is reduced emphasis on long-term storage, what we refer to as a traditional perspective of permanence. Instead, each considers shorter periods of time—up to and including single year harvest deferrals—as eligible project commitments. Here, we provide a brief discussion of the historical permanence and accounting literature, with an emphasis on contradictory views and how these perspectives have evolved over time. Next, we quantitatively assess the long-term influence of different permanence requirements as envisioned in several new and existing forest carbon programs, estimating net mitigation across a variety of forest types and project configurations. We conclude with a presentation of our quantitative findings in the context of the existing literature, while also highlighting unmet research needs on these so-called new offsets, those emerging novel approaches for forest carbon mitigation that challenge the research and practice status quo.